The changing role of science in the innovation process: From Queen to Cinderella? - Mendonça, S. (Technological Forecasting and Social Change, 2009)
An overview of how the role of science in relation to innovation has been defined over the past five decades is given, showing a change from a linear to a chain-linked model of interpretation. A third analytical grid, leading to a new model is proposed, summarizing the current research on the nature of economically useful knowledge, the diversity of intervening players in learning and the outcomes of innovation. While the chain-linked view surpassed the linear model by emphasising that science is part of the process but not necessarily the initiating step, we need today to explicitly acknowledge the multi-player dimension of innovation and the wider institutional setting where distinct forms of learning take place. The reason is simple: almost all high added value products embody elements of scientific knowledge. But science is only one of a plurality of other sources of knowledge that induce innovation-based growth. More attention should also be given to understanding markets and organisations.